A density functional theory study on lewis acid‐catalyzed transesterification of β‐oxodithioesters. Issue 13 (17th March 2014) - Guo, Xiaokang; Chen, Lihui; Zhu, Yanyan; Zhang, Anqi; Wei, Donghui; Tang, Mingsheng
<x xml:space="preserve">Abstract</x> The detailed mechanisms of the Lewis acid‐catalyzed transesterification of β‐oxodithioesters at a solvent‐free condition were studied using density functional theory. Five possible reaction pathways, including one noncatalyzed (channel 1) and four Lewis acid‐catalyzed channels (SnCl2‐catalyzed channels 2 and 3 and SnCl2·2H2O‐catalyzed channels 4 and 5), were investigated. Our calculated results indicate that the energy barriers of the catalyzed channels are significantly lower than that of channel 1. Channel 5, which has an energy barrier of 33.70 kcal/mol as calculated at the B3LYP/[6‐31G(d, p)+LANL2DZ] level, is the most energy‐favorable channel. Moreover, one water molecule of SnCl2·2H2O participated in the transesterification in channel 5. Thus, we report a novel function of the SnCl2·2H2O catalyst, which is quite different from the function of the conventional nonhydrated Lewis acid SnCl2. To understand the function of these two Lewis acid catalysts better, the global reactivity indexes and natural bond orbital charge were analyzed. This work helps in understanding the function of the Lewis acid in transesterification, and it can provide valuable insight for the rational design of new Lewis acid catalysts. © 2014 Wiley Periodicals, Inc.